Students' mental health : the personality inventory for children: grades 1- 5 - Abou Chedid, Kamal (Beirut Lebanese Association for Educational Sciences; Kuwait Society for the advancement of Arab, 2008)
This chapter dealt with the cognitive, emotional and behavioral functions of children enrolled in the primary first to fifth grade after the July war of 2006 on the basis of the results of Children s Personality Index in the Lebanese version that observes physical disorders, rebellion and disobedience, domestic violence, learning difficulties and other psychological disorders. The research aims to map children s psychological conditions in the primary stage; analyze these conditions as they relate to the extent of exposure to the July War in addition to a number of social and demographic variances; and extract the impact of exposure and the corresponding clinical context.
: Chapter in a Book
Keywords: Children; Cycle primaire; Elementary Education; Enfants; Psychological Health; Santé psychologique